Uczeń w szeregach rzemieślniczych. System edukacyjny i wychowawczy chłopców w wileńskich cechach w dobie wczesnonowożytnej w świetle statutów cechowych - Manyś, Bernadetta (Biuletyn Historii Wychowania, 2019)
In this paper, I analyse the educational and teaching systems developed for boys joining Vilnius craft workshops. The boys worked (participating in production) and prepared themselves for their future profession. In my paper, I present the educational and teaching paths leading to an apprentice assuming the status of a fellow. It is interesting how the students operated in the structures of the guild workshops and what skills they possessed. The research does not encompass the sons of master craftsmen and out-of-guild craftsmen who would come to Vilnius and attempt to join the craft guilds. These issues require a separate analysis. It was not my intention to provide a holistic study of the issue; rather, I revised and supplemented Józef Morzy’s research in which he partly analysed craft guilds in Vilnius with respect to the essential work skills. In my analysis, I made use of the statutes of the craft guilds operating in Vilnius, one of the biggest cities in the Polish-Lithuanian Commonwealth, in the early modern period.